Analisis Sistem Informasi Manajemen Proyek : Systematic Literature Review - Andika, Irfan; Lim, Steven; Nevile, Steven; Satya, Richard; Farisi, Ahmad (Universitas Multi Data Palembang, 2024)
Project planning, execution, and control are part of the Project Management Information System, which helps to ensure that time, budget, and project-specific requirements are met effectively and efficiently. It is expected that the use of project management information systems can improve operational efficiency, organizational structure, and the level of transparency. This study aims to analyze the methods typically used in project management information system research over the past five years. This is expected to facilitate project progress monitoring, asset management, and strategic decision-making, all of which play an important role in overall project progress. The Systematic Literature Review (SLR) method was used in this research to systematically identify, review, evaluate, and interpret the collected research. From the results of researching 10 journals on the topic of project management information systems in the span of 2018 to 2023, it can be seen that the most commonly used methods are the waterfall method and the most dominant field in using project management information systems is the contractor sector.